2020
DOI: 10.1002/app.49256
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of organic–inorganic intumescent flame retardant with phosphorus, nitrogen and silicon and its flame retardant effect for epoxy resin

Abstract: According to the requirement of fire life cycle assessment (LCA), chitosan ethoxyl urea phosphate (CEUP), an organic–inorganic intumescent flame retardant (IFR) containing phosphorus, nitrogen, and silicon, was synthesized by the reaction of chitosan, phosphorus pentoxide, and urea. FTIR, 1H NMR, SEM, and XRD were employed to characterize the compounds. As a result, CEUP was successfully prepared with higher thermal stability, favorable to enhance fire resistance. Combined with OMMT, the organic/inorganic IFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…After the polymerization reaction among HCCP and DDS was completely finished, the synthesized CP‐DDS microsphere exhibited a broad absorption at about 2 θ = 20° corresponding to the amorphous phase, and no crystalline peaks were observed. These results indicated that CPDDS microsphere had a highly cross‐linked structure that correlated to its high thermal stability 36 …”
Section: Resultsmentioning
confidence: 77%
“…After the polymerization reaction among HCCP and DDS was completely finished, the synthesized CP‐DDS microsphere exhibited a broad absorption at about 2 θ = 20° corresponding to the amorphous phase, and no crystalline peaks were observed. These results indicated that CPDDS microsphere had a highly cross‐linked structure that correlated to its high thermal stability 36 …”
Section: Resultsmentioning
confidence: 77%
“…As for PA, a wide peak at around 3335 cm −1 is owing to stretching vibration of ─OH. The signal at 1120 cm −1 is associated with P═O stretching, 31 while absorption peaks located at 1019 and 891 cm −1 are respectively corresponding to symmetric stretching and asymmetric vibration of P─O(H) 32 . For PIPT, the intensity of ─OH peak at around 3335 cm −1 is significantly reduced in comparison with that of PA.…”
Section: Resultsmentioning
confidence: 95%
“…By adding inorganic materials into organic materials, the physical properties of organic materials could be improved, including hardness, strength, thermal stability, and chemical stability. [6][7][8][9] The introduction of inorganic particles or their graed modied particles into UF resin might form certain chemical bonds between them, which improves the chemical stability of the resin, reduces the consumption of chemical raw materials such as urea and formaldehyde and improves the environmental performance of resin and wood-based panels.…”
Section: Introductionmentioning
confidence: 99%